2013
DOI: 10.1136/archdischild-2012-302881
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing in childhood disorders

Abstract: Genetics has been revolutionised by recent technologies. The latest addition to these advances is next-generation sequencing, which is set to transform clinical diagnostics in every branch of medicine. In the research arena this has already been instrumental in identifying hundreds of novel genetic syndromes, making a molecular diagnosis possible for the first time in numerous refractory cases. However, the pace of change has left many clinicians bewildered by new terminology and the implications of next-gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…The formed ends are adenylated and adaptor oligonucleotides are added to the ends of these adenylated fragments. These adaptors are short oligonucleotides of known sequences for universal priming of both amplification and sequencing steps [5]. Commonly, the fragments are enriched for specific genes of interest (targeted sequencing), or for all coding regions (whole exome capture for WES), in a physical capture step.…”
Section: Whole Exome Capture and Sequencingmentioning
confidence: 99%
See 2 more Smart Citations
“…The formed ends are adenylated and adaptor oligonucleotides are added to the ends of these adenylated fragments. These adaptors are short oligonucleotides of known sequences for universal priming of both amplification and sequencing steps [5]. Commonly, the fragments are enriched for specific genes of interest (targeted sequencing), or for all coding regions (whole exome capture for WES), in a physical capture step.…”
Section: Whole Exome Capture and Sequencingmentioning
confidence: 99%
“…Commonly, the fragments are enriched for specific genes of interest (targeted sequencing), or for all coding regions (whole exome capture for WES), in a physical capture step. That enrichment is not needed for WGS and all fragments are sequenced [5].…”
Section: Whole Exome Capture and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several miRNAs are demonstrated that associated with OA development and modulation such as miR-18a (chondrocyte differentiation), miR-27b (controlling the expression of MMP-13), miR-34a (prevention of cartilage degradation), miR-140 and miR-222 (controlling cartilage homeostasis), miR-146 (promotion of inflammatory OA), miR146a (OA cartilage pathogenesis), miR-675 (cartilage repair) [30, 31]. With the development of NGS technology, changes in the expression levels of thousands of genes and miRNAs can be examined simultaneously, and integral analysis of the dysregulated genes can be performed to obtain information regarding pathogenic mechanisms of OA at the cellular level, animal model and human disease [32, 33]. Furthermore, NGS data can be used to discover novel molecular diagnostic markers and therapeutic targets [34].…”
Section: Introductionmentioning
confidence: 99%
“…In the latter case this is often because of a lack of identified candidate genes. In these cases, exomic/genomic sequencing of panels of known genes causing EIEEs will identify a considerable number . Although more expensive than some investigations, the cost benefit is likely to be dramatically better than previous technology.…”
mentioning
confidence: 99%